2022
DOI: 10.3389/fmicb.2022.900948
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crucial Amino Acid Residues for Antimicrobial Activity of Angiogenin 4 and Its Modulation of Gut Microbiota in Mice

Abstract: Angiogenin 4 bearing ribonuclease activity is an endogenous antimicrobial protein expressed in small and large intestine. However, the crucial amino acid residues responsible for the antibacterial activity of Ang4 and its impact on gut microbiota remain unknown. Here, we report the contribution of critical amino acid residues in the functional regions of Ang4 to its activity against Salmonella typhimurium LT2 and the effect of Ang4 on gut microbiota in mice. We found that Ang4 binds S. typhimurium LT2 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Therefore, the alterations of these beneficial and harmful microbes indicate significant synergistic effects of combination therapy on gut microbiota modification. However, not all of the potential beneficial microbes that were decreased in HFD can be reversed by combined treatment, such as Lactobacillus, Clostridium_sensu_stricto_1 and Coriobacteriaceae _UCG-002 ( Kong et al, 2019 ; Sultana et al, 2022 ). Notably, Akkermansia, as a beneficial microbiota, showed different trends in the metformin and pioglitazone monotherapy groups and was slightly increased in the combined treatment group, which suggests another form of complementary action between metformin and pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the alterations of these beneficial and harmful microbes indicate significant synergistic effects of combination therapy on gut microbiota modification. However, not all of the potential beneficial microbes that were decreased in HFD can be reversed by combined treatment, such as Lactobacillus, Clostridium_sensu_stricto_1 and Coriobacteriaceae _UCG-002 ( Kong et al, 2019 ; Sultana et al, 2022 ). Notably, Akkermansia, as a beneficial microbiota, showed different trends in the metformin and pioglitazone monotherapy groups and was slightly increased in the combined treatment group, which suggests another form of complementary action between metformin and pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…mAng4 demonstrates antibacterial effects against Bacteroides thetaiotaomicron, Enterococcus faecalis, Bifidobacterium longum, Enterococcus gallinarum, Listeria monocytogenes, and Salmonella typhimurium LT2 (Hooper et al, 2003;Walker et al, 2013). Recent 10.3389/fmicb.2022 Frontiers in Microbiology 07 frontiersin.org studies showed that disruption of bacterial membrane is needed to kill bacteria by mAng4 (Sultana et al, 2022). In addition, mAng4 has been attributed to angiogenesis, which is determined by the evaluation of ex vivo angiogenesis through thoracic aorta assay (Crabtree et al, 2007).…”
Section: Biological Functions Of Angiogenins In Humans and Micementioning
confidence: 99%
“…However, Lys59 in mAng4 seems to be crucial for angiogenic activity, since the substitution of Lys59 → Asn59 by mutation abolished angiogenic activity ( Crabtree et al, 2007 ). In addition, structural modification of the cell-binding segment has no appreciable effect on RNase activity ( Crabtree et al, 2007 ; Sultana et al, 2022 ).…”
Section: Structures Of Hang and Mangsmentioning
confidence: 99%
See 2 more Smart Citations